GIS-based Multi-criteria Assessment of Areas Suitable for the Construction of a Repository for Low and Intermediate Kevel Radioactive Waste in Slovenia - Gregorčič, Tim; Krevs, Marko; Repe, Blaž (Geographica Pannonica, 2024)
This study evaluates the site selection for a new repository for low and intermediate lev- el radioactive waste in Slovenia. The ordered weighted average method is used in combi- nation with the TOPSIS method to evaluate the current site and its alternatives considering eight criteria and five constraints. The results show that 52.37% of the country’s area falls into five suitability classes for the two decision alternatives, while others do not fulfil the cri- teria at all. In both cases, the most suitable areas are located in the north-eastern part of Slovenia. The current site tends to be less suitable (categorised as moderately suitable and very unsuitable) and should be reassessed by the relevant stakeholders.